Impact of cilostazol on clinical outcomes in lower extremity arterial disease patients after angioplasty: A real-world analysis - Hsien-Yuan Chang; Hui-Wen Lin; Po-Wei Chen; Sheng-Hsiang Lin; Ting-Hsing Chao; Yi-Heng Li (PLoS ONE, 2025)
Background Cilostazol has been shown to improve walking distance in patients with lower extremity arterial disease (LEAD) and may reduce restenosis after revascularization. However, its long-term prognostic impact in real-world settings remains underexplored. Methods We conducted a retrospective cohort study using data from Taiwan's National Health Insurance Research Database (2012–2022). We included stable LEAD patients who had undergone percutaneous transluminal angioplasty (PTA) and remained event-free for 1 year. Stabilized inverse probability of treatment weighting (IPTW) was applied to adjust for baseline confounders. The study aimed to evaluate the effect of cilostazol on major adverse cardiovascular events (MACE), major adverse limb events (MALE), and composite bleeding outcomes. Results Among 5,300 stable LEAD patients, of whom 844 received cilostazol alone, 1,786 received aspirin or clopidogrel, and 2,670 received cilostazol combined with aspirin or clopidogrel. After IPTW, there were no significant differences between cilostazol monotherapy and any antiplatelet therapy groups regarding MACE, MALE, or composite bleeding outcomes (aHR [95% CI] = 0.84 [0.68–1.03], p = 0.09; 0.84 [0.70–1.01], p = 0.06; 0.88 [0.71–1.10], p = 0.26, respectively). In secondary outcomes, cilostazol treatment was associated with a reduced rate of subsequent angioplasty (aHR [95% CI] = 0.80 [0.60–0.98], p = 0.03). There were no significant differences in clinical outcomes when comparing cilostazol monotherapy to cilostazol combined with antiplatelet therapy. Conclusion In this real-world Asian cohort, cilostazol showed similar prognostic benefits and safety compared to standard antiplatelet therapy. These findings support its role in the long-term management of LEAD patients following PTA, particularly in Asian populations.